방사선사의 병원감염예방에 대한 인지도와 수행도에 관한 연구 - 여진동; Jindong Yeo; 전병규; Byeongkyu Jeon (Journal of the Korean Society of Radiology, 2012)
본 연구는 방사선사의 병원감염관리에 대한 인지도와 수행도를 파악하여 병원감염관리 방안의 개선 및 교육을 위한 기초자료를 제공하기 위해 실시한 연구이다. 연구대상자의 병원감염관리에 대한 인지도와 수행도의 평균 평점은 150점 만점으로 인지도 141.05점과 수행도 138.15점으로 모든 영역에서 인지도가 높을수록 수행도가 높은 정상관계를 보였으나 인지도에 비해 수행도가 전체적으로 낮음을 확인 할 수 있었다. 인지도에 영향을 미치는 요인으로는 감염관리 교육의 필요성, 감염예방 교육여부, 환자의 질병상태 인지 여부 등으로 통계적으로 유의하게 나타났고, 수행 도에 영향을 미치는 요인으로는 감염예방 교육여부, 환자의 질병상태 인지여부, 인지도 등으로 통계적으로 유의하게 나타났다. The purpose of this study is to examine radiologists' awareness and performance of hospital infection control, providing basic information needed to improve and educate how to control hospital infection. The subjects' awareness and performance of hospital infection control were respectively 141.05 and 138.15 points in average score on a 150-point scale. In all sub-areas of the control, the higher the awareness was, the higher the performance was, but the latter was relatively lower than the former. Factors that were having statistically significant effects on that awareness included the necessity of infection control education, participation or non-participation in infection prevention education and recognition or non-recognition of patients' disease state. And factors that were having statistically significant influences on that performance included participation or non-participation in infection prevention education, recognition or non-recognition of patients' disease state and the foresaid awareness itself.